REPRESENTASI FEMINISME DALAM FILM ‘GANGUBAI KATHIAWADI’ - Miswa L, Rifqa Imelda (JURNAL AL-IJTIMAIYYAH, 2023)
Abstract: The social phenomenon that places women in a lower position than men in power relations is an important issue that is often discussed in the context of the struggle for gender equality. However, women's struggle against attachment to power relations is also a relative and contextual social phenomenon. In the Indian context, women in countries that still maintain patriarchal structures often face difficulties and difficult experiences. Patriarchy refers to a social system that gives greater power and control to men in various aspects of life, including in political, economic, cultural and social matters. Women struggle not to be looked down upon or looked down upon, regardless of their position, profession or social status. Those who feel shackled by patriarchal culture and masculine domination are referred to as the feminist movement. Film ‘Gangubai Kathiawadi’ and the characters used as data sources in this study are material objects, while the formal subject of the research is a critical discourse about the characters behind the portrayal of feminism in films. The purpose of this research is to find out the depiction of feminism in the film ‘Gangubai Kathiawadi’. The researcher uses Roland Barthes' theory to describe the combination of characters and the rules behind them to create meaning from the text. Roland Barthes's levels of meaning are denotation, meaning and myth. In addition, theories and parameters to see the understanding of gender in film, gender analysis and social construction theory by Peter L. Berger & Thomas Luckman. The results of the analysis in this study found that there is a sign of the construction of women in scene film ‘Gangubai Kathiawadi’. This is the impact of patriarchal culture and structural poverty that occurs in India. Based on the meaning through Barthes' three sign systems; denotation, connotation, and myth found the existence of symbols and signs of representation of liberal feminism in the film ‘Gangubai Kathiawadi’.Keywords: Representation; Feminism; Film; Semiotics.Abstrak: Fenomena sosial yang menempatkan perempuan pada posisi yang lebih rendah dari laki-laki dalam hubungan kekuasaan adalah isu penting yang sering dibahas dalam konteks perjuangan kesetaraan gender. Tetapi, perjuangan perempuan untuk melawan keterikatan pada hubungan kekuasaan tersebut juga merupakan fenomena sosial yang relatif dan kontekstual. Pada konteks India, perempuan di negara-negara yang masih mempertahankan struktur patriarki sering menghadapi kesulitan dan pengalaman yang sulit. Patriarki merujuk pada sistem sosial yang memberikan kekuasaan dan kontrol yang lebih besar kepada laki-laki dalam berbagai aspek kehidupan, termasuk dalam hal politik, ekonomi, budaya, dan sosial. Perempuan berjuang untuk tidak dipandang sebelah mata apalagi rendah terlepas dari apapun posisi, profesi, maupun status sosial mereka. Mereka yang merasa terbelenggu oleh budaya patriarki dan dominasi maskulin ini disebut sebagai gerakan feminis. Film ‘Gangubai Kathiawadi’ dan karakter yang dijadikan sumber data dalam penelitian ini adalah objek material, sedangkan subjek formal penelitian adalah wacana kritis tentang karakter di balik penggambaran feminisme dalam film. Tujuan dari penelitian ini adalah untuk mengetahui penggambaran feminisme dalam film ‘Gangubai Kathiawadi’. Peneliti menggunakan teori Roland Barthes untuk menguraikan kombinasi karakter dan aturan dibaliknya untuk menciptakan makna dari teks. Tingkatan makna Roland Barthes adalah denotasi, makna dan mitos. Selain itu, teori dan parameter untuk melihat pemahaman gender dalam film, analisis gender dan teori konstruksi sosial oleh Peter L. Berger & Thomas Luckman. Hasil analisis dalam penelitian ini ditemukan bahwa adanya tanda konstruksi perempuan dalam scene film ‘Gangubai Kathiawadi’. Hal ini merupakan dampak dari budaya patriarki dan kemiskinan struktural yang terjadi di India. Berdasarkan pemaknaan melalui tiga sistem tanda Barthes; denotasi, konotasi, dan mitos ditemukan adanya simbol dan tanda representasi feminisme liberal dalam film ‘Gangubai Kathiawadi’.Kata Kunci: Representasi; Feminisme; Film; Semiotika.